Improving furosemide polymorphs properties through supramolecular complexes of beta-cyclodextrin - Garnero, Claudia (2014)
Fil: Garnero, Claudia. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Unidad de Investigación y Desarrollo en Tecnología Farmacéutica; Argentina.